2019
DOI: 10.1001/jamanetworkopen.2019.3209
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Prescriptions Among Commercially Insured Individuals at High Risk of Opioid Overdose

Abstract: IMPORTANCE As opioid-related mortality continues to increase, naloxone remains a critical intervention in preventing overdose death. Opportunities to expand access through the health care setting should be optimized. OBJECTIVE To determine the characteristics of naloxone prescribing for US patients at high risk of opioid overdose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 25 publications
1
51
1
Order By: Relevance
“… 11 Although naloxone access laws were estimated to increase naloxone dispensing, 36 a recent study found that only 2135 of 138 108 high-risk patients (1.5%) in the US were prescribed naloxone in 2016. 37 This finding suggests that policies designed to dramatically improve treatment for overdose are needed.…”
Section: Discussionmentioning
confidence: 99%
“… 11 Although naloxone access laws were estimated to increase naloxone dispensing, 36 a recent study found that only 2135 of 138 108 high-risk patients (1.5%) in the US were prescribed naloxone in 2016. 37 This finding suggests that policies designed to dramatically improve treatment for overdose are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Interprofessional collaborations and education in interventions about opioid risk counseling and naloxone prescribing have proven to be effective and should be implemented and devised for enhanced patient safety. [67][68][69][70] National associations would then have an added opportunity to facilitate adoption of best practices and competencies for pharmacists dispensing naloxone. With this information, state associations can create education programs that align with state-specific regulations regarding standing orders and naloxone dispensing.…”
Section: Discussionmentioning
confidence: 99%
“…This study suggests that PDMP mandates may prevent adolescents from beginning down the path of opioid addiction and IDU, which is important to consider alongside evidence that PDMPs could prompt people who are already using opioids to transition to illicit substances [27]. Enactment of PDMP mandates could complement other evidence-based interventions, such as expanded addiction treatment [44,45], naloxone distribution [46,47], safe prescribing interventions [48], and harm reduction services [49].…”
Section: Plos Medicinementioning
confidence: 95%